Reactions of Arylcarbenes with Lewis Acids. Issue 68 (9th November 2018) - Raut, Akshay Hemant; Costa, Paolo; Sander, Wolfram
Abstract: The reactions of the three triplet ground state arylcarbenes diphenylcarbene1, fluorenylidene2, and dibenzocycloheptadienylidene3 with the Lewis acids H2 O, ICF3, and BF3 were studied under the conditions of matrix isolation. H2 O was selected as typical hydrogen bond donor, ICF3 as halogen bond donor, and BF3 as strong Lewis acid. H2 O forms hydrogen‐bonded complexes of the singlet carbenes with1 and2, but not with3 . This is rationalized by the larger singlet–triplet gap of3, which does not allow to stabilize the singlet state below the triplet state by hydrogen bonding. With ICF3, both1 and3 form halogen‐bonded complexes of the singlet states of the carbenes. This indicates that halogen bonding stabilizes singlet carbenes more than hydrogen bonding. Carbene2 reacts differently from1 and3 by forming an iodonium ylide, thus avoiding antiaromatic destabilization of the fluorenyl unit. With BF3, all three carbenes form zwitterionic Lewis acid/base complexes. Abstract : The closed shell singlet states of arylcarbenes are very strong Lewis basis that are efficiently stabilized by interactions with Lewis acids.